Characteristics of Silica Nanoparticles from Rice Husk as Influenced by Surface Modification with Used Solvent Containing Silane - Kendri Wahyuningsih; Sri Yuliani; Hoerudin Hoerudin (Journal of Engineering and Technological Sciences, 2021)
Silica extracted from rice husk (silica nanoparticles, Si-NP RHA) has great potential for industrial use, particularly as filler in the rubber industry. However, silica is poorly dispersed in the matrix and needs to be modified by a silane linking agent (bis-(3-triethoxysilylpropyl) tetrasulfane (TESPT)) to improve its mixing properties. As a result, a large amount of used solvent containing silane TESPT is produced. This study aimed to evaluate the surface modification of silica nanoparticles from rice husk employing this used solvent and to characterize the particles’ physical properties. Silica nanoparticles were extracted from rice husk using a sol-gel method. FTIR spectography demonstrated that the TESPT on fresh solvent and the used solvent were successfully grafted onto the surface of Si-NP RHA. Si-NP RHA modified by Two Step Modification (TSM) employing used solvent had strong absorption peaks at wave numbers of 2927.94 cm-1 and 1446.61 cm-1, which are associated with vibration of the ‑CH2 group and deforming vibration of the -C-H group in TESPT compounds. Likewise, Si-NP RHA modified with One Step Modification (OSM), either using fresh solvent or the used solvent, exhibited absorption peaks at wave numbers 2935.66 cm-1 and 1404.18 cm-1. The result showed that the used solvent still effectively modified the silica nanoparticle surface.